Few-layer SrRu2O6 nanosheets as non-van der waals honeycomb antiferromagnets: implications for two-dimensional spintronics - Homkar, Suvidyakumar; Chand, Bharat; Rajput, Shatruhan Singh; Gorantla, Sandeep; Das, Tilak; Babar, Rohit; Patil, Shivprasad; Klingeler, Rüdiger; Nair, Sunil; Kabir, Mukul; Bajpai, Ashna (ACS applied nano materials, 2021)
The current family of experimentally realized two-dimensional magnetic materials, based on 3d transition metal ions, possesses weak spin-orbit coupling. In contrast, we report a novel platform in a chemically bonded and layered oxide SrRu2O6. In bulk, this system is known for strong electron correlations and competing spin-orbit coupling. We present the synthesis and characterization of ultrathin nanosheets of SrRu2O6 along with first-principles calculations to explore their magnetic state. SrRu2O6 nanosheets are synthesized using a scalable technique of liquid exfoliation. Atomic force microscopy reveals that the thickness of the nanosheets varies between three and five monolayers. Experimental data also suggest that exfoliation occurs from the planes perpendicular to the c-axis wherein the intervening hexagonal Sr lattice separates the two-dimensional Ru honeycomb. The high-resolution transmission electron microscopy images indicate that the average interatomic spacing between the Ru layers is slightly reduced, which agrees with the density functional theory (DFT) calculations. The signatures of rotational stacking of the nanosheets are also observed. Within the first-principles calculations, we show that antiferromagnetism survives in these nanosheets. The experimental realization of graphene-like two-dimensional (2D) sheets of SrRu2O6 offers enormous possibilities to explore emergent properties associated with a magnetic honeycomb with large spin-orbit coupling, and this system is likely to have applications in the area of antiferromagnetic spintronics.
Im Titel sind die Zahlen 2 und 6 tiefgestellt
Gesehen am 17.11.2021